2019
DOI: 10.1016/j.trsl.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A proof-of-concept clinical trial using mesenchymal stem cells for the treatment of corneal epithelial stem cell deficiency

Abstract: Ocular stem cell transplantation derived from either autologous or allogeneic donor corneoscleral junction is a functional cell therapy to manage extensive and/or severe limbal stem cell deficiencies that lead to corneal epithelial failure. Mesenchymal stem cells have been properly tested in animal models of this ophthalmic pathology, but never in human eyes despite their potential advantages. We conducted a 6-to 12month proof-of-concept, randomized, double-masked pilot trial to test whether allogeneic bone ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 57 publications
1
75
0
1
Order By: Relevance
“…Mesenchymal stem cells (MSCs) are multipotent stromal cells that have been shown to have high potential for disease treatment, e.g., Crohn's disease, ocular disorders, spinal cord injuries, and cartilage repair [1][2][3][4][5]. Furthermore, MSCs have been shown to target tumors and their microenvironment, and potentially play a role in tumor cell therapy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent stromal cells that have been shown to have high potential for disease treatment, e.g., Crohn's disease, ocular disorders, spinal cord injuries, and cartilage repair [1][2][3][4][5]. Furthermore, MSCs have been shown to target tumors and their microenvironment, and potentially play a role in tumor cell therapy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Human immature dental pulp stem cells, embryonic stem cells and umbilical cord stem cells also showed good results in animal models (50,51). One study (52) compared results between allogenic CLET and allogenic bone marrow-derived mesenchymal transplant (MSCT). They included 11 patients who underwent allogenic CLET and 17 who had MSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Among the several paracrine factors produced by MSCs, tumour necrosis factor-a-stimulated gene 6 (TSG-6) has been shown to be necessary for MSCs to deliver their anti-inflammatory effects [141]. An inhuman, proof-of-concept, randomised, doubleblind controlled trial demonstrated possible equivalency of allogeneic MSC therapy and allogeneic CLET in the treatment of bilateral stage II/III LSCD [142]. Primary end points included corneal epithelial opacification, integrity (presence of persistent defects), and cell morphology (as measured by IVCM).…”
Section: Cultivated Oral Mucosa Epithelia Transplant (Comet)mentioning
confidence: 99%